In vitro biomechanical study on the figure-of-eight and Kessler sutures in swine flexor tendons - Kawachi, Diogo Thomaz [UNESP]; Deienno, Francisco Simões [UNESP]; Varanda, Denis [UNESP]; Cortopassi, Andrea Christina [UNESP]; Sardenberg, Trajano [UNESP] (Thieme, 2020)
Objective To evaluate the biomechanical properties of the figure-of-eight and Kessler suture techniques for tendons. Methods Flexor tendons of porcine fingers were divided into two groups with triple central figure of eight sutures (six passages) and Kessler sutures (two passages) associated with simple and continuous peripheral sutures, and submitted to continuous longitudinal mechanical tests, to obtain the mechanical properties of maximum load and energy at maximum load. Results The mean maximum load and energy at maximum load in the figure-of-8 suture were of 63.4 N and 217.3 N.mm respectively; in the Kessler suture, the values were of 34.19 N and 100.9 N.mm respectively. The statistical analysis indicated that the figure-of-eight suture is mechanically superior to the Kessler technique. Conclusion Under the conditions of this experiment and in the flexor tendon of porcine fingers, the triple figure-of-eight suture (six passages) is more resistant than the Kessler suture (two passages). The figure-of-eight suture with six passages enables active movement in the immediate rehabilitation of the flexor tendon repair of the finger, with little risk of rupture or suture spacing.
Keywords: biomechanical phenomenon; finger injuries; orthopedic procedures; suture techniques; tendon injuries